Implementation of definite screening design in optimization of in situ hydrolysis of EFB in cholinium acetate and locally produced cellulase combined system - Elgharbawy, Amal A.; Alam, Md Zahangir; Kabbashi, Nassereldeen Ahmed; Moniruzzaman, Muhammad; Jamal, Parveen (Springer, 2017)
Purpose Ionic liquids (ILs) have been found to be highly promising for lignocellulosic biomass pretreatment, due to their excellent abilities to dissolve biopolymers. However,they have found to inactivate enzymes. In previous studies,Cholinium-based ILs showed great compatibility with cellulases and thus were introduced for a combined-system. This study aims to find the optimum condition in order to achieve the maximum pretreatment-hydrolysis of empty fruit bunches (EFB). Methods Definitive screening design (DSD) was employed with seven factors that are thought to impact the process including pretreatment temperature, pretreatment time, hydrolysis time, enzyme loading, particle size, biomass loading, and IL/buffer ratio. DSD offered several solutions for optimization in which they were experimentally tested. Results The maximum sugar concentration (77 g/L) was obtained at 90 C, 70–116 min of treatment, 36–42 h of hydrolysis, 40–62 Unit/g cellulase loading, 34–35 %, w/v) biomass loading, 220–450 l particle size, and 10 % (v/v) IL to buffer ratio, respectively. The subsequent optimization by response surface methodology (RSM) revealed the temperature for treatment can drop to 75 C while fixing the pretreatment time at 100 min. Around 75 unit/g of cellulase and [22.0 % (w/v) of the biomass could be loaded to achieve a minimum of 70.0 ± 7.83 g/L of sugar, equivalent to 0.38 ± 0.08 g glucose/g and 0.48 ± 0.05 g total reducing sugar/g dry EFB. Conclusions The locally produced cellulase (PKC-Cel) from Trichoderma reesei exhibited promising results in the single-step process and can be used as an efficient approach to be optimized for fermentation to bioethanol production.